PENGEMBANGAN PROGRAM APOTEK HIDUP DAN PERBAIKAN INFRASTRUKTUR JALAN DI DESA DUMOLODO - Suleman Mile; Tri Setiawati Maulana; Divia A. Paputungan; Silvana Kaloko; Mutmainah Latabi; Sri Jeinta; Anggun Fitriyana Rahayu; Elsya Amalia Nur Misali; Erik Rahim Dama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explore and implement community development programs in Dumolodo Village, Gentuma Raya District, North Gorontalo Regency, focusing on the “Living Pharmacy” initiative and road infrastructure improvement. The methods involved community observation, data collection, and participatory program planning with local stakeholders. Results indicate successful establishment of home-based medicinal plant gardens (Living Pharmacy) and partial improvement of village roads, enhancing health awareness, accessibility, and socio-economic activities. Community responses were positive, reflecting increased knowledge and participation. The study concludes that well-structured community programs can effectively empower local residents, support sustainable development, and promote local health and economic welfare.